Rodinný dům - Leupold, Karel (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Bakalářská práce řeší návrh rodinného domu ve městě Telč. Jedná se o dvoupodlažní dům částečně podsklepený, střecha je sedlová se sklonem 35°. Dům je navržen z cihelných tvarovek POROTHERM. Budova je osazena na mírně svažitém pozemku. Objekt je navržen podle platných norem.

Bachelor´s thesis solve design of the Family house in city Telč. It is a two-storey house with a partial basement, the roof is pitched with a slope of 35°. The house is designed of brick POROTHERM. The building is set on a land slightly sloping. The object is designed by valid standard.
Family house
Keywords: Rodinný dům; terasa; schodiště; suterén; garáž; okno; dveře; strop; komín; zeď; podlaha; zábradlí; patro; střecha; Family house; terrace; staircase; basement; garage; window; door; ceiling; chimney; wall; floor; railing; upstairs; roof